Penerapan Model Pembelajaran Tuntas dengan Metode Tutor Sebaya untuk Meningkatkan Hasil Belajar Matematika Siswa SMP - Khusnul Khotimah; Rita Yuliastuti (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2019)
This research is motivated by the low student mathematics learning outcomes. The reason is the lack of full delivery of lessons and students have not fully understood the material. One alternative to overcome this problem is to implement a complete learning model with peer tutoring methods. The purpose of this study: 1) to describe the improvement of students 'mathematics learning outcomes through the application of a complete learning model with material peer tutoring methods to construct flat-side space for junior high school students, 2) to describe students' responses to the application of the complete learning model with peer tutoring methods. classroom action research with quantitative and qualitative descriptive analysis. Research location in Tuban 7th Middle School. The subjects studied were students of class VIII E. The instruments used were learning outcome evaluation test sheets and student response questionnaires. The results of the study concluded that students' mathematics learning outcomes in the application of the complete learning model with peer tutoring methods had increased. This can be seen from the average student learning outcomes of the first cycle of 88, the second cycle of 89 and the third cycle of 97. So there is an increase in the average mathematics learning outcomes in the first cycle to the second cycle of 1 and from cycle II to cycle III amounting to 8. And the percentage of classical completeness in cycles I, II and III reach 100%. While the student response to the application of the complete learning model with peer tutors is included in the criteria very effective, with a percentage of positive responses of 96% and the percentage of negative responses of 4%.